THE USE OF PERSONAL PHOTOGRAPHS IN IMPROVING STUDENTS’SKILLS IN WRITING DESCRIPTIVE TEXT - Indrajaya, Valdy; Apriliaswati, Rahayu; Sutapa Y, Y Gatot (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research was conducted to improve descriptive text writing of seventh grade students of SMP Negeri 17 and their use of noun phrases, simple present tense, and sentences writing in descriptive text by using personal photographs. The research was conducted in form of classroom action research. Subject of the research was seventh grade students of VII B class of SMP Negeri 17 Pontianak of academic year 2016/2017. In this research, the students made improvement during teaching and learning process as well as in writing descriptive text by using personal photographs. The students could also improve their use of noun phrases and simple present tense as well as their sentences writing in descriptive text by using personal photographs. After that, the students enjoyed and were happy in using personal photographs in their learning process as well as in writing descriptive text. Therefore, it indicated that personal photographs improved descriptive text writing of seventh grade students of VIIB of SMP Negeri 17. Keywords: personal photographs, writing, descriptive text.